Induction of Ankrd1 in Dilated Cardiomyopathy Correlates with the Heart Failure Progression. (16th April 2015) - Bogomolovas, Julius; Brohm, Kathrin; Čelutkienė, Jelena; Balčiūnaitė, Giedrė; Bironaitė, Daiva; Bukelskienė, Virginija; Daunoravičus, Dainius; Witt, Christian C.; Fielitz, Jens; Grabauskienė, Virginija; Labeit, Siegfried
Abstract : Progression of idiopathic dilated cardiomyopathy (IDCM) is marked with extensive left ventricular remodeling whose clinical manifestations and molecular basis are poorly understood. We aimed to evaluate the clinical potential of titin ligands in monitoring progression of cardiac remodeling associated with end-stage IDCM. Expression patterns of 8 mechanoptotic machinery-associated titin ligands ( ANKRD1, ANKRD2, TRIM63, TRIM55, NBR1, MLP, FHL2, and TCAP ) were quantitated in endomyocardial biopsies from 25 patients with advanced IDCM. When comparing NYHA disease stages, elevated ANKRD1 expression levels marked transition from NYHA < IV to NYHA IV. ANKRD1 expression levels closely correlated with systolic strain depression and short E wave deceleration time, as determined by echocardiography. On molecular level, myocardial ANKRD1 and serum adiponectin correlated with low BAX/BCL-2 ratios, indicative of antiapoptotic tissue propensity observed during the worsening of heart failure. ANKRD1 is a potential marker for cardiac remodeling and disease progression in IDCM. ANKRD1 expression correlated with reduced cardiac contractility and compliance. The association of ANKRD1 with antiapoptotic response suggests its role as myocyte survival factor during late stage heart disease, warranting further studies on ANKRD1 during end-stage heart failure.